Atributos para análise do índice de caminhabilidade na área central de Petrolina-PE - Pinheiro, Aline Gonçalves (Universidade do Vale do Rio dos Sinos, 2020)
Non-motorized trips, whether on foot or by bicycle, interact much more with the urban space, in addition to representing a lower cost for users, for the environment and for society. The emergence of the principles of Sustainable Urbanism validates the concept of walkability and inserts it in discussions about mobility, planning and urban design, and focuses on the conditions of urban space seen from the perspective of pedestrians. The term walkability refers to the extent to which the characteristics of the urban environment favor its use for walking. The methodologies for assessing walkability appear in this context to help in several issues transversal to urban mobility, with the purpose of investigating the effects of walking in the prevention of physical and mental health, crime, air pollution, among other contemporary issues related to life urban. The objective of this research is to analyze the walking conditions of spaces for pedestrians to use in central areas of medium-sized cities, in order to understand the physical and / or subjective aspects that promote or inhibit walking, analyzing the characteristics of urban space in the central area of Petrolina city, from the proposition and application of a qualitative method of assessing walkability. In order to test the application of the index, a case study was carried out in a central area of the city of Petrolina-PE. After applying the index and analyzing the technical data sheets, it was possible to investigate the conditions of comfort, fluidity and safety of public spaces for pedestrians, their deficiencies and potential, social and economic relations on the street scale and offering to the municipal urban management subsidies for the elaboration of the guidelines for the intervention project in the studied area information that allows identifying which actions should be implemented in the short, medium and long term to improve these spaces and their uses.
Keywords: Urbanismo; Caminhabilidade; Vegetação urbana; Urbanism; Walkability; Urban vegetation; ACCNPQ::Ciências Sociais Aplicadas::Arquitetura e Urbanismo